Ameliorative Effects of Curcumin on 5-Fluorouracil-Induced Liver and Kidney Toxicity in Rats - Ismael, Hawkar Fadhil; Salih, Shelanah (Sulaimani Journal for Pure and Applied Sciences, 2025)
5-Fluorouracil is a widely used chemotherapeutic drug associated with significant systemic toxicity, particularly affecting highly metabolic organs such as the liver and kidney. This toxicity limits its clinical efficacy. Curcumin, a natural polyphenol derived from turmeric (Curcuma longa), has demonstrated potent antioxidant, anti-inflammatory, and anti-apoptotic properties. This study investigates the protective effects of curcumin against 5-FU-induced hepatotoxicity, nephrotoxicity, and hematotoxicity in rats. For this purpose, 25 rats were subdivided into five groups of five animals each and treated for five weeks: the first group received tap water every day by gavage, while the second group received 5-FU (20 mg/kg BW twice a week) through an intraperitoneal injection. Groups 3, 4, and 5 followed the same treatment as the second group but also received daily doses of curcumin dissolved in corn oil (150, 300, and 450 mg/kg BW, respectively). At the end of the study, liver, kidney, and blood samples were collected to assess histological changes and biochemical parameters (ALT, AST, ALP, ALB, Cr, BUN, blood cells, and hemoglobin). The results showed that giving 5-FU caused a significant increase (p < 0.05) in serum levels of ALT, AST, ALP, BUN, and CRP, while it greatly reduced blood cells and hemoglobin. Curcumin significantly (p < 0.05) reversed the effect of 5-FU in that parameter. Histopathological analysis of the liver and kidney confirmed these findings, and curcumin supplementation, particularly in the CUR150+5-FU and CUR300+5-FU groups, greatly attenuated the 5-FU-induced biochemical and histopathological changes.
Keywords: 5Fluorouracil; curcumin; antioxidant; hepatotoxicity; antiinflammatory; nephrotoxicity